Evaluation of wound healing activity of Hibiscus rosa sinensis linn in albino rats - Gala, Monil Yogesh Neena; Pathak, Swanand S. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: From debridement to the appearance of healthy granulation tissue is the maximum time during which the patient suffers more economically and psychologically. Due to high cost expenditure in hospitalisation, dressing material cost and loss of daily earnings during this period which puts a psychological pressure over patient and family especially in India where majority of the population is still below poverty line. Also access to quick treatment is yet not possible to majority of population living in rural with no access to basic healthcare. Methods: It was an experimental study wherein Wistar rat models were used to check for the wound healing property of Hibiscus Rosa Sinensis (HRS) compared with one of the common standard drugs of treatment for available today, betadine. To observe the wound healing property of the HRS flower extract, the experiment was divided into 2 parts i.e. excision wound model and incision wound model. The groups were treated with respective medication along with a control group of rats. Results: At the end of the experiment, it was observed that HRS flower extract increased the wound breaking strength as compared to control but not as effectively as compared to the betadine ointment. Conclusions: HRS flower extract helps in early epithelization and helps in decreasing the wound size. Betadine is associated with adverse events like life threatening allergic reactions, water retention, etc.